The Idea of Male Female Partnership Inside Cry the Peacock: Exploring the Dichotomy of Male-Female Partnership in Anita Desai's Cry the Peacock (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Anita Desai is a standout amongst the most influentialcontemporary Indian Novelists in English. She is concerned with the internaluniverse of her characters. She tries to search for the profound cravings,feelings and emotions felt by her characters and demonstrates to them as theaffecting element behind their activity. Her depiction of male-femalepartnership is affected and molded by complex social milieu .She essentiallydepicts the predicament of current lady in the existing man overwhelmedpublicly accepted norms where she endeavors to voice herself. She fundamentallydepicts the dissimilarity in temperament as influencing the male-femalepartnership. This paper advances the depiction of ladies in male-femalepartnership. For the most part lady are customarily and also enthusiasticallysubject to man and any disturbance in partnership turns out to be a misfortuneof self .It is through ones partnership that one assesses his/her worth.